Orality, literacy, and the Lisu linguistic borderlands - Arrington, Aminta (Missiology, 2015)
The Lisu, one of China’s 55 ethnic groups, converted to Christianity nearly 100 years ago through the evangelistic efforts of the China Inland Mission (CIM). The CIM missionaries constructed an orthography, translated the Bible, and stressed the importance of Scripture for individual religious devotion. However, in the course of five months of fieldwork in the Nujiang Valley, I rarely encountered a Lisu engaged in personal Bible study. I contend that this situation has less to do with the level of faith or commitment, and more to do with the interplay of literacy and orality, of individual and community, and the overall Lisu linguistic situation. While the Lisu Bible provides the overall frame for Lisu Christian society, it does not sustain Lisu Christianity in the everyday arena: the practical living out of what it means to be a Lisu Christian. While Scriptures provide the necessary framework, something needs to fill in the frame, to provide sustenance to nurture faith in an oral context. For societies and ethnic groups existing in the linguistic borderlands between the oral and the written, this is the missiological task that will remain once Bible translation is complete.